Pengembangan Model Pembelajaran Role Playing dalam Meningkatkan Perilaku Belajar Mahasiswa Mata Kuliah Patologi Sosial - Jas, Jaspar; Achmad, Said Suhil; Alvi, Ria Rizkia (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2020)
This development research aims to determine the initial conditions of student learning behavior in the social pathology course and to develop a role playing learning model in improving student learning behavior in the social pathology course at the Penmas Study Program, FKIP UNRI. This research procedure is a research and development (R & D), with qualitative data analysis techniques. The flow of the model development process is a preliminary study (literature study, field study of the Role playing learning model that occurs, description and analysis of findings) and development study (development of role playing learning models, and worksheets), validation of development experts and hypothetical models of the results. validation). Data collection techniques using observation with observation sheets. The data validity technique was performed by triangulation, discussion with experts, and extension of observations. The data analysis technique used in this research is qualitative data analysis, namely data reduction, data presentation, and conclusion drawing. The results showed that the initial conditions of student learning behavior showed that students did not have good learning behavior in the learning process and the results of validation of the role playing learning model showed that the model was feasible to be tested in a limited and wider manner in the learning process. The final model in this research and development is the formulation of a hypothetical role playing model from the validation results.